"Violent and Not Quite Modern?": Lascars and Everyday Resistance Across the Sail–Steam Divide. (May 2019) - Manjrekar, Naina
Abstract : By exploring forms of maritime resistance spanning the age of sail and steam, this article interrogates certain preponderant assumptions within the historiography of subaltern agency. Within this historiography, "modernity" has generally come to be signalled by trade union organisation and a concomitant regard for legality, while violent resistance is implicitly or explicitly taken to signify the Other of modernity: traditional, primitive, incomplete. Arguing that this tradition/modernity divide has mapped onto the sail–steam divide in the historiography of maritime resistance, this article complicates the association of violent mutiny with the age of sail and litigiousness with the age of steam. It does this by bringing both epochs into single focus, thereby finding important continuities in forms of everyday resistance on board ship across the sail-steam divide. Using existing scholarship to look at resistance in the age of sail and archival material like ships' logbooks, newspapers and "Lascari"–English dictionaries for the age of the steam, it argues that rather than trade unions fundamentally reshaping the forms of everyday resistance into legal channels, it was in fact these longer traditions of quotidian contestation that fed into the formation of unions at the end of World War I, and continued through the 1920s and 1930s.